Effects of previous severe exercise on two and three parameter critical power modeling - Eduardo Kokubun; Fernando Roberto de-Oliveira; Jefferson Rosa Cardoso; Herbert Gustavo Simões; Edilson Serpeloni Cyrino; Nilo Massaru Okuno; Camila Ferreira Infante Rosa; Fábio Yuzo Nakamura (Universidade Federal de Santa Catarina, 2007)
The purpose of this study was to apply the two and three-parameter critical power model equations after depletion of a fi xed amount of anaerobic work capacity (AWC), followed by a short rest period. Sixteen subjects underwent: (1) two practice trials for ergometer familiarization to severe exercise; (2) 4-5 exercise bouts on different days for the estimation of critical power (CP) and AWC using the two and three parameter models; (3) the same procedures as described in stage 2 were repeated after 30 s recovery from 180 s of exercise completed at an intensity that would have elicited exhaustion in around 300 s. The CP2parameter (130-174 W versus 131-170 W) and CP3parameter (108 versus 100 W) estimated after prior severe exercise followed by a short rest period remained stable compared to the fatigue-free tests. The AWC2parameter was reduced in response to prior severe exercise. The AWC3parameter was not significantly reduced. The correlations between CP2parameter derived from the same equation with and without prior AWC2parameter reduction were strong (r = 0.97-0.99, P <0.001). The correlation was merely moderate (r = 0.62, P = 0.01) when CP3parameter was analyzed. It can be concluded that the two-parameter critical power model provides a coherent mathematical description of the reduced mechanical output induced by a prior fatiguing task, since AWC2parameter was affected while CP2parameter estimates remained constant. ABSTRACT O propósito do presente estudo foi aplicar as equações do modelo de potência crítica de dois e três parâmetros após a depleção de uma quantia fi xa de capacidade de trabalho anaeróbio (AWC), seguido de um período curto de repouso. Dezesseis sujeitos realizaram: (1) duas familiarizações ao exercício severo no cicloergômetro; (2) 4-5 exercícios máximos em dias diferentes para a estimativa da CP e AWC por meio dos modelos de dois e três parâmetros; (3) os mesmos procedimentos descritos no #2 foram realizados após 30 s de repouso e de um exercício de 180 s a uma intensidade em que a exaustão provavelmente ocorreria em ~300 s. A CP2parameter (130-174 W versus 131-170 W) e CP3parameter (108 versus 100 W) estimadas após o exercício prévio severo e seguido por um curto período de repouso permaneceu estável quando comparado às estimativas sem o exercício prévio. A AWC2parameter foi diminuída em resposta ao exercício prévio severo. A AWC3parameter não foi significativamente reduzida. As correlações entre CP2parameter derivados da mesma equação com e sem a redução prévia da AWC2parameter foram fortes (r = 0,97-0,99; P < 0,001). Para a CP3parameter a correlação foi somente moderada (r = 0,62; P = 0,01). Assim, pode ser concluído que o modelo de potência crítica de dois parâmetros promove descrições matemáticas coerentes quando é induzido um exercício prévio, sendo que a AWC2parameter foi alterada enquanto que a estimativa da CP2parameter permaneceu constante.